Analysis of the Concept and Implementation of Local Taxes and Levies in Indonesia: Challenges and Impacts on Local Revenues - Andito Dipontoro Wibisono; Angga Bayu Putra; Muhammad Rafly Aprilyo; Galuh Tresna Murti (Universitas Muhammadiyah Makassar, 2023)
This paper aims to examine the concept of local taxes and levies that apply in Indonesia based on the law. This is because many people are still unfamiliar with the understanding of local taxes and levies. Local taxes and levies are part of local revenue that can be used to support various local government activities. Local taxes and levies can be in the form of taxes, excise, levies, and others. This study uses a qualitative descriptive method, which involves extracting information through observation, descriptive analysis and conclusion drawing. The results of the study show that local taxes and levies in Indonesia have a complex and diverse structure, and this makes the management of local taxes and levies in Indonesia difficult. Whereas local taxes and levies themselves are one of the main sources for local revenue. In addition, problems such as unclear rules, lack of personnel competence, legal uncertainty, and other issues also affect the management of local taxes and levies in Indonesia